Investigation of Crushing Behavior of Polystyrene Coated Spherical Shaped Aluminum Foams - UZUN, Arif (Bitlis Eren Universitesi Fen Bilimleri Dergisi, 2020)
In this study, the crushing behavior of spherically shaped aluminum foam pieces coated with polystyrene and uncoated under compression load was investigated. The spherical shaped aluminum foam parts produced by powder metallurgy with diameters of 8 mm and 10 mm were coated with polystyrene by the injection molding process. The obtained foam elements were then subject to quasi-static compression tests at room temperature with a constant cross head speed of 1 mm/min. According to the experimental results, polystyrene coatings increased the energy damping capacity of the foams by approximately 115% while increasing the density by about 50%.
Keywords: Küresel şekilli alüminyum köpük; Gözenekli malzeme; Basma özellikleri; Polistiren; Engineering; Mühendislik; Spherical shaped aluminum foam; Porous material; Compressive properties; Polystyrene